Comparison of anticomplement immunofluorescence and fluorescent antibody-to-membrane antigen tests for determination of immunity status to varicella-zoster virus and for serodifferentiation of varicella-zoster and herpes simplex virus infections. - Gallo, D (1981)
The anticomplement immunofluorescence (ACIF) test was compared with the fluorescent antibody-to-membrane antigen (FAMA) test for determining varicella-zoster virus antibody levels as a measure of varicella-zoster virus immunity status. The ACIF test was found to be comparable to the FAMA test in sensitivity and could be used for examining sera at low dilutions of 1:2 and 1:4. In addition, the ACIF method proved to be a more economical procedure in terms of antigen required and personnel time necessary to perform the test. Heterologous varicella-zoster virus antibody titer rises were demonstrated by the FAMA test with 10 serum pairs from patients with clinically diagnosed genital herpes simplex virus infection, indicating that the FAMA test is no more suitable than other serological methods for serodifferentiation of those herpes simplex virus and varicella-zoster virus infections in which antibody increases occur to both antigens.